2017
DOI: 10.30699/jidai.29.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Biological Significance of Immunohistochemical Expression of Osteopontin and Ki67 in Fibro-osseous lesions of jaws

Abstract: Background and Aim: Fibrous dysplasia (FD) and ossifying fibroma (OF) are the most important fibro-osseous lesions (FOLs) of the jaws with similarities in radiographic and morphological features while showing completely different biological behavior. Limited studies have been evaluated immunohistochemistry markers, such as osteopontin (OPN) and osteocalcin to help differentiate these two lesions. This study aimed to assess the immunoexpression of OPN and Ki67 as potential markers for differentiation of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…These data are in full agreement with studies reported in literature. 26,27 The association between the weak marking of Ki67 epithelial cells and lesions' unicolor and multilocular radiological aspects could be explained by the fact that, apart from cementoosseous dysplasia, the majority of lesions are dominated by ameloblastomas which can be multilocular or unilocular on radiography. 19,23 In addition, the association described between the weak Ki67 marking of ameloblastomas epithelial cells and cemento-osseous dysplasia could be explained by the fact that these lesions are slow-growing ones (low proliferative index) with perceptible clinical expression after several months of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in full agreement with studies reported in literature. 26,27 The association between the weak marking of Ki67 epithelial cells and lesions' unicolor and multilocular radiological aspects could be explained by the fact that, apart from cementoosseous dysplasia, the majority of lesions are dominated by ameloblastomas which can be multilocular or unilocular on radiography. 19,23 In addition, the association described between the weak Ki67 marking of ameloblastomas epithelial cells and cemento-osseous dysplasia could be explained by the fact that these lesions are slow-growing ones (low proliferative index) with perceptible clinical expression after several months of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Benign Fibro-osseous lesions' (BFOLs) is a generic term that includes a group of diseases affecting jaw and facial bones (Slootweg et al, 2005) which are recognized histologically by the process in which normal bone is replaced by mesenchymal tissue with proliferating fibroblast-like cells and few collagen bundles together with variable quantity of newly formed calcified tissue (Sargolzaei et al, 2017). These include: fibrous dysplasia (FD), osseous dysplasia, and ossifying fibroma (OF) and their subtypes (Slootweg et al, 2005).…”
Section: Introductionmentioning
confidence: 99%